PENERAPAN MODEL PEMBELAJARAN MEA (MEANS END ANALYSIS) DALAM MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN AQIDAH AKHLAK - Dadang Sahroni; Ojim; Miswan Ramdani; Yadi Setiawan; Ivo Milawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low motivation of students in the learning process is a problem that is often encountered in the field, including in the Aqidah Akhlak subject. This study aims to determine: (1) the description of the implementation of the MEA (Means End Analysis) learning model; (2) the description of students' cognitive learning motivation; and (3) the magnitude of the influence of the MEA learning model on students' learning motivation in Aqidah Akhlak subject for Grade IX at MTs Persis 68 Sukabumi City. The method used is an experimental method with a quantitative approach. The study population consisted of 40 students with a sample of 20 students. The instrument used was a questionnaire consisting of 15 items for the MEA learning model variable and 15 items for the learning motivation variable. Data were analyzed using path analysis at a significance level of α = 0.05. The results showed that: (1) the majority of students (70%) were in the moderate learning motivation category, 15% in the high category, and 15% in the low category; (2) the coefficient of determination (R Square) of 0.436 indicates a contribution of 43.6% to student learning motivation; and (3) the influence of the MEA learning model on students' learning motivation was 43.6%, which is classified as sufficient. Thus, the implementation of the MEA learning model has a sufficiently significant influence in improving students' learning motivation in the Aqidah Akhlak subject.